Development of 3D printable self-sensing cementitious composites. (27th June 2022) - Wang, Lining; Aslani, Farhad; Mukherjee, Abhijit
Highlights: 3D printable cementitious composite with enhanced sensing capability was developed. The 3D printed cementitious composites exhibited distinct mechanical anisotropy. 3DP can orientate the fibre and contribute to the conductive path formation. Fibre alignment improves the linearity and repeatability of the piezoresistivity. Abstract: This paper explores the potential of fabricating self-sensing cementitious composites using the 3D printing technology. In this study, carbon fibre (CF) and activated carbon powder (ACP) were studied at various concentrations as functional fillers. An extrusion-based 3D printer was used for 3D printed samples preparation and the mould cast samples were fabricated as a direct comparison. The mechanical properties, electrical resistivity and piezoresistive performance in two directions were measured. The results indicate that 3D printing technology can achieve fibre alignment within the printed filament and, consequently, result in anisotropic behaviour of the 3D printed composites. The optimal mechanical strength with compressive strength of 74.9 MPa and flexural strength of 16.4 MPa were achieved by 3D printed composite with hybrid CF at 0.7 wt% and ACP at 0.25 wt%. The optimal 3D printed composite shows an excellent piezoresistive response with improved linearity, repeatability and signal quality when the loading direction is perpendicular to the printing direction, demonstrating a strong fit with the predicted equation. On the microstructural level, scanning electron microscopy images indicated the fibre alignment and enhanced fibre–matrix bonding of 3D printed composites.